DUKUNGAN AKADEMIK, DUKUNGAN SOSIAL, DUKUNGAN SOSIAL, DAN PENDIDIKAN KEWIRAUSAHAAN SEBAGAI FAKTOR KONTEKSTUAL YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA - Herwiek Diyah Lestari Herwiek; Andhi Johan S (Majalah Imiah Manajemen & Bisnis, 2020)
This study aims to analyze the Effect of Contextual Factors on Student Entrepreneurial Interest. This research was conducted at the Faculty of Economics and Business Students Wijayakusuma University Purwokerto. The number of samples used was 80 respondents, and the sampling technique using purposive sampling method. To determine the sample size using a method developed by Isaac and Michael, as well as Krejcie and Morgan. The analytical tool used is Multiple Linear Regression (Multiple Regression). The results of the analysis using a 95% confidence level (α = 0.05) and degree of freedom (df) = (n-k) = (80-5) = 75, the t table is 1.992 < of t arithmetic for each independent variable are Academic Support (th1 = 2.852), Social Support (th2 = 2.341), Environmental Support (th3 = 6.776), and Entrepreneurship Education (th4 = 6.967) . When compared then th1, th2, th3, th4> t Table, so that Ho is rejected. This can mean that Academic Support, Social Support, Environmental Support, and Entrepreneurship Education each significantly influence Entrepreneurial Interest. This shows that the better the Academic Support, Social Support, Environmental Support, and Entrepreneurship Education provided, the more it will increase the interest of students of the Faculty of Economics and Business for entrepreneurship.